2015
DOI: 10.2147/ijwh.s50804
|View full text |Cite
|
Sign up to set email alerts
|

Critical appraisal of paroxetine for the treatment of vasomotor symptoms

Abstract: BackgroundVasomotor symptoms (VMS), characterized by hot flashes and night sweats, are the most commonly reported symptoms associated with estrogen deficiency during menopause and occur in up to 70% of women. The goal of treatment is to reduce the frequency and severity of symptoms. Although hormone therapy (HT) is generally recommended as first-line treatment, it is not appropriate for all patients. Antidepressants, specifically selective serotonin reuptake inhibitors, have been evaluated and utilized interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(23 citation statements)
references
References 26 publications
2
20
0
1
Order By: Relevance
“…This is in addition to the three wide‐ranging reviews conducted before the licensing of Brisdelle . Both of these recent reviews included most of the six trials we identified, plus some others, and reached similar conclusions . However, our review has several advantages over the others that enhance the reliability and interpretation of the data.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…This is in addition to the three wide‐ranging reviews conducted before the licensing of Brisdelle . Both of these recent reviews included most of the six trials we identified, plus some others, and reached similar conclusions . However, our review has several advantages over the others that enhance the reliability and interpretation of the data.…”
Section: Discussionsupporting
confidence: 55%
“…Thirdly, we have used the GRADE approach to rate the quality of evidence, which helps in the interpretation of the results of the systematic review. Although the results of the two recent reviews and this review are similar, the interpretation using GRADE clarifies the evidence.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…For example, compared with the 75% reduction in VMS frequency and 89% reduction in VMS severity observed with HT, 2 gabapentin results in a 45% reduction in frequency and 54% reduction in severity . After 6–12 weeks of treatment, paroxetine treatment results in a 33–67% reduction in frequency and desvenlafaxine results in a 65% reduction in frequency . Gabapentin and paroxetine have been compared with each other, with clinical trial results illustrating a 55–68% reduction in VMS with gabapentin compared with a 20–23% reduction with paroxetine.…”
Section: Pharmacologic Treatmentsmentioning
confidence: 99%
“…In a separate study, paroxetine 7.5 mg daily was shown to improve hot flashes without weight gain or sexual dysfunction (45).…”
Section: Selective Serotonin Re-uptake Inhibitors (Ssris)mentioning
confidence: 95%